2016
DOI: 10.1007/s00170-015-8110-2
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar metal joining of stainless steel and titanium using copper as transition metal

Abstract: Joining of stainless steel and titanium dissimilar metal combination has a specific interest in the nuclear industry. Due to the metallurgical incompatibility, it has been very difficult to produce reliable joints between these metals due to the formation of FeTi and Fe 2 Ti types of intermetallic compounds. The metallurgical incompatibility between both materials is enhanced by the time-temperature profile of the welding process used. Brittle intermetallics (IMCs) are formed during FeTi welding (FeTi and Fe 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 11 publications
(11 reference statements)
2
21
0
1
Order By: Relevance
“…When the process was modelled using Thermo-Cal, the results showed that within the bonding temperature range studied (850-900 • C) four binary phases are possible; Cu3Ti2, Cu 2 Ti, Ti 2 Cu, and Cu 4 Ti 3 , as shown in Figure 10A, support the EDS data. Similar observations were reported by Pardal et al [3] who studied dissimilar metal joining of Ti and duplex stainless steel using Cu as a transition metal interlayer. A plot of the Gibbs free energy profile shown in Figure 10C,D indicates that several stable phases are likely to form in the Ti-Cu binary system for the bonding temperature range studied.…”
Section: Eds Line Scans Presented Insupporting
confidence: 87%
See 1 more Smart Citation
“…When the process was modelled using Thermo-Cal, the results showed that within the bonding temperature range studied (850-900 • C) four binary phases are possible; Cu3Ti2, Cu 2 Ti, Ti 2 Cu, and Cu 4 Ti 3 , as shown in Figure 10A, support the EDS data. Similar observations were reported by Pardal et al [3] who studied dissimilar metal joining of Ti and duplex stainless steel using Cu as a transition metal interlayer. A plot of the Gibbs free energy profile shown in Figure 10C,D indicates that several stable phases are likely to form in the Ti-Cu binary system for the bonding temperature range studied.…”
Section: Eds Line Scans Presented Insupporting
confidence: 87%
“…The growth in the demand for higher-performing multicomponent structures and mechanical systems necessitates the combination of these advanced alloys into superstructures containing multiple materials of uniquely differing chemical, thermal, and thermomechanical properties [1,2]. Currently, structures made with materials of similar types are joined using traditional welding technologies such as arc welding [3], laser welding [4], spark plasma welding [5], ultrasonic welding [6], etc. The welding of multiple components of structures is still an area that requires extensive research to identify technologies that are capable of welding dissimilar materials without adverse effects given the differences in the properties of the materials [7].…”
Section: Introductionmentioning
confidence: 99%
“…7: Welding zone microstructure CONCLUSION CMT welding is suitable for joining of heterogeneous materials (Poláková, et al 2017). In Pardal et al 2016, the resulting weld strength values were in the range of approximately 50 - 200 MPa. Pardal heat input evaluates the dominant parameter during the study.…”
Section: : Tensile Test Resultsmentioning
confidence: 99%
“…Good results in the tensile test were achieved only in using the welding parameters designated as a). The d) and e) parameters did not show a sufficient tensile strength due to the formation of fragile compounds between FeTi and Fe2Ti (Pardal 2016). The results of the tensile tests using the welding parameters designated as a) were very similar.…”
Section: Metallographic Analysis Equipmentmentioning
confidence: 85%
See 1 more Smart Citation